Penggunaan Metode Bercerita Interaktif dalam Pembelajaran Kerjasama Anak Usia Dini - Maghfirah, Wulan Suci (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
Teachers and parents have an important role in instilling attitudes towards early childhood, one of which is to instil cooperation in various learning activities for early childhood that will later impact the lives of children in the future, because by instilling collaboration can train children's ability to respect others, train children communicate and train children in relationships. One of the activities that can be done is an interactive storytelling method where the teacher tells a story or story in which there are life values ??that can be instilled in early childhood. This study aims to determine the use of interactive storytelling methods in collaborative learning in mother's kindergarten. Storytelling is a very interesting method for kindergarten children, because through the story the teacher can enter messages that can motivate the child, the teacher makes the story more interesting and fun for the child so that the collaboration message that can be conveyed from the content of the story can be with easy to understand children. This study uses a qualitative descriptive method, with the focus of research on the Use of Interactive Storytelling Methods in Collaborative Learning in Kindergarten Bhakti Middle Aceh District School Year 2018/2019, while the primary data source is the Bhakti Ibu Kindergarten teacher and 15 children from Class B .2. The secondary data sources are documentation, books, journals, school environment. Data collection techniques using observation, interview and documentation techniques. Checking the validity of the data using triangulation. The results of the study show that the application of interactive storytelling methods has been done well from starting to prepare concepts, implementation, and evaluation. Teachers play a very important role in children's collaboration learning. The results of using interactive storytelling methods in learning children's collaboration can be seen from children who start to enjoy playing or doing things simultaneously.